Analysis of Factors Affecting the Income of Dodol MSMEs After the Operation of the Toll Road: A Case Study in Bengkel Village, Perbaungan District, Serdang Bedagai Regency - Syahfitri, Dea; Hasanah, Uswatun; Ramadhan, Anggia (Journal of Economics and Social Sciences (JESS), 2025)
Dodol MSMEs are an important economic sector in the village, but they face challenges after the toll road began operating. This study aims to determine the factors that affect the income of dodol MSMEs after the toll road began operating. The indicators used in this study are labor, innovation, price, product promotion, business location, use of technology, impact of the toll road, service, and product quality. This study uses a quantitative method with purposive sampling technique. Data in this study were collected through questionnaires and analyzed using multiple linear regression analysis. The results of this study indicate that the variables of labor and business location have a positive and significant effect on the income of dodol MSMEs after the operation of the toll road in Bengkel Village, Perbaungan District, Serdang Bedagai Regency. The results of this study are expected to provide recommendations for the government and MSME actors to increase income and develop the dodol business in Bengkel Village, Perbaungan District, Serdang Bedagai Regency.